Cognitive performance and long-latency auditory evoked potentials: a study on aging - Ferreira de Oliveira, Maria de Fatima; Menezes, Pedro de Lemos; Lins Carnauba, Aline Tenorio; Pereira, Liliane Desgualdo; Lira de Andrade, Kelly Cristina; Figueiredo Frizzo, Ana Claudia [UNESP]; Soares, Ilka do Amaral (Hospital Clinicas, Univ Sao Paulo, 2021)
OBJECTIVE: To evaluate the relationship between cognitive performance and long-latency auditory evoked potentials in an elderly population. METHODS: The sample consisted of adults between 20 and 58 years of age and elderly adults between 60 and 70 years of age. The screening procedures adopted were an inspection of the external auditory canal, tonal and vocal audiometry, tympanometry, brain stem auditory evoked potential, the Montreal Cognitive Assessment test, and long-latency auditory evoked potential. RESULTS: The latency and amplitude values of cortical components by age group showed significant differences under the following conditions: (i) signals evoked by the speech stimulus /da/ and by the pure-tone stimulus at 2,000 Hz for the N2 amplitude (p=0.008 and p=0.001, respectively), which were both higher for adults, and (ii) signals evoked by the speech stimulus /da/ for N1 latency (p=0.018) and by the pure-tone stimulus at 2,000 Hz for P2 latency (p=0.017), which were both higher in the elderly population. The cognitive component (P300) showed a significant difference when evoked by speech stimuli, with higher latency in the elderly population (p=0.013). When correlated with cognitive processes, the latency and amplitude of cortical potentials showed direct and medium-strength correlations between abnormal scores obtained on the Montreal Cognitive Assessment test and P2 amplitude (p < 0.001 and r=0.452). CONCLUSION: There is a relationship between long-latency potentials and cognitive performance in the elderly, which was observed by the increase in the P2 amplitude and the impairment of the process of sound decoding.
Keywords: Evoked potentials; Cognitive Dysfunction; Aging